2012
DOI: 10.5742/mejim.2011.55149
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Male Oligospermia Glycoconjugate Inhibin B Hormone and A - L - Fucose in Kurdistani ( Iraq ) Populations

Abstract: Objectives-To assess the role of inhibin B in the evaluation of male factor infertility as a prospective study. To determine normative levels of inhibin B and examine levels in relationship to FSH, sperm count, and motility in a cohort of fertile and infertile men from the Kurdistan region of Iraq. Materials and methods-Semen analysis was performed according to World Health Organization guidelines. An ELISA technique were applied for serum levels of inhibin B (ng/L), LH (mIU/L), FSH (mIU/L), and testosterone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Furthermore, since it has been suggested that serum inhibin B in relation to male and female reproductive health have been published internationally and the risk of leukemia that may spread to other organs like ovary (Ahmed et al, 2001;Wen et al, 2006;Lee et al, 2008;Moos et al, 2009;Taflan et al, 2011;Dillon and Gracia, 2012), the present study attempt to clarify the correlation between inhibin and serum protein, glutathione and the two vitamins E and C in patients with ALL, the results were reanalyzed by using linear regression analysis, Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since it has been suggested that serum inhibin B in relation to male and female reproductive health have been published internationally and the risk of leukemia that may spread to other organs like ovary (Ahmed et al, 2001;Wen et al, 2006;Lee et al, 2008;Moos et al, 2009;Taflan et al, 2011;Dillon and Gracia, 2012), the present study attempt to clarify the correlation between inhibin and serum protein, glutathione and the two vitamins E and C in patients with ALL, the results were reanalyzed by using linear regression analysis, Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of infertility varies widely, being less in developed countries and more in developing countries where limited resources for investigation and treatment are available [4]. Infertility is an important medical and social problem in the world as regards 15% of couples are infertile and 40% are infertile because of male factor infertility and 40% are because of female factor infertility and in the remainder both factors are associated [5].…”
Section: Introductionmentioning
confidence: 99%
“…The results also showed that low (74.5 mg/kg) and moderate (235.6 mg/kg) of isoflavones produced a significant (p < 0.05) increase in serum AMH levels while high (1046.6 mg/kg) produced a non-significant (p > 0.05) increase in serum AMH levels in post pubertal rats. The increased levels of antimullerian hormone might have been due to the stimulatory effect on the Sertoli cells by isoflavones as shown in an in vivo study by [22].…”
Section: Effect Of Soy Isoflavone Administration On Serum Anti-mullermentioning
confidence: 99%